Ovarian tumors: the specific features of evolution, extent, diagnosis, and prevention - P. G. Prokopenko; S. A. Borisenko; V. S. Poltoranina; V. M. Shelepova; A. A. Terentyev (ABV-press, 2014)
The paper describes a range of embryo proteins, the potential markers for ovarian tumors. More than 10 new embryo proteins have been tested; however, a strictly specific protein has not been found to diagnose ovarian tumors. Serum oncoovarian -1-globulin is shown to remain the most promising marker today. Noteworthy are the specific features of evolution and the mechanism of the early extent of a tumor process. The role of pregnancy in preventing ovarian tumors is considered. An attempt has been made to understand the causes of the disease and the mechanisms of its development.